Who are the women who enrolled in the POSITIVE trial: A global study to support young hormone receptor positive breast cancer survivors desiring pregnancy. (October 2021) - Partridge, Ann H.; Niman, Samuel M.; Ruggeri, Monica; Peccatori, Fedro A.; Azim, Hatem A.; Colleoni, Marco; Saura, Cristina; Shimizu, Chikako; Sætersdal, Anna Barbro; Kroep, Judith R.; Mailliez, Audrey; Warner, Ellen; et al.
Abstract: Background: Premenopausal women with early hormone-receptor positive (HR+) breast cancer receive 5–10 years of adjuvant endocrine therapy (ET) during which pregnancy is contraindicated and fertility may wane. The POSITIVE study investigates the impact of temporary ET interruption to allow pregnancy. Methods: POSITIVE enrolled women with stage I-III HR + early breast cancer, ≤42 years, who had received 18–30 months of adjuvant ET and wished to interrupt ET for pregnancy. Treatment interruption for up to 2 years was permitted to allow pregnancy, delivery and breastfeeding, followed by ET resumption to complete the planned duration. Findings: From 12/2014 to 12/2019, 518 women were enrolled at 116 institutions/20 countries/4 continents. At enrolment, the median age was 37 years and 74.9 % were nulliparous. Fertility preservation was used by 51.5 % of women. 93.2 % of patients had stage I/II disease, 66.0 % were node-negative, 54.7 % had breast conserving surgery, 61.9 % had received neo/adjuvant chemotherapy. Tamoxifen alone was the most prescribed ET (41.8 %), followed by tamoxifen + ovarian function suppression (OFS) (35.4 %). A greater proportion of North American women were <35 years at enrolment (42.7 %), had mastectomy (59.0 %) and received tamoxifen alone (59.8 %). More Asian women were nulliparous (81.0 %), had node-negative disease (76.2%) and received tamoxifen + OFS (56.0 %). More European women had received chemotherapy (69.3 %). Interpretation: The characteristics of participants in the POSITIVE study provide insights to which patients and doctors considered it acceptable to interrupt ET to pursue pregnancy. Similarities and variations from a regional, sociodemographic, disease and treatment standpoint suggest specific sociocultural attitudes across the world. Highlights: Fertility and pregnancy are priority concerns for young breast cancer survivors. POSITIVE explores a transient interruption of endocrine therapy to allow conception. Patients' characteristics highlight features considered suitable to study enrolment. Overall, patients enrolled had a relatively high median age and low-risk disease. Variations emerged across continents suggesting specific sociocultural attitudes.